Digital Pattern for Worker Welfare Management for an Organization in Thai Supply Chain - Artaphon Chansamut (ExcelingTech, 2023)
The objective of research study were to study pattern of digital for worker welfare management for organization in Thai supply chain and evaluation of the model . The sample group in this study consisted of ten experts using purposive sampling. Data were analysed by arithmetic mean and standard deviation. The research findings model six elements namely main components, Supplier, organization , Satisfaction and service, Customers satisfaction and feedback. The ten experts agree that pattern of digital for worker welfare management for organization in Thai supply chain was high suitability which mean that pattern of digital for worker welfare management for organization in Thai supply chain may be applied in worker welfare to support the tasks..